Hyper-Reflecting Foci in Multiple Sclerosis Retina Associate With Macrophage/Microglia-Derived Cytokines in Cerebrospinal Fluid - Puthenparampil, Marco; Torresin, Tommaso; Franciotta, Silvia; Marin, Annachiara; De Napoli, Federica; Mauceri, Valentina Annamaria; Miante, Silvia; Pilotto, Elisabetta; Midena, Edoardo; Gallo, Paolo (Frontiers in Immunology, 2022)
Background Increasing evidence suggests that retinal hyper-reflecting foci (HRF) might be clusters of activated and proliferating microglia. Since microglia are widespread activated in multiple sclerosis (MS) brain, its evaluation in retina may help to understand and monitor MS-related pathology. Aim This study aims at investigating the association of HRF with cerebrospinal fluid (CSF) cytokines and MRI parameters in relapsing–remitting MS (RRMS). Methods Nineteen RRMS at clinical onset and 15 non-inflammatory neurological disorders (NIND) underwent brain 3T MRI and CSF examination. Optical coherence tomography (OCT) analysis, including HRF count, was performed on RRMS patients. Sixty-nine cytokines/chemokines were analyzed in the CSF by multiplex technology. Results In RRMS, HRF count in the ganglion cell layer (GCL) was associated with IL-1Ra, IL-9, IL-15, IFN-γ, and G-CSF. Moreover, in RRMS patients CSF concentrations of IL-1Ra and G-CSF associated with global cortical thickness. The HRF count in the inner nuclear layer (INL) correlated with IL-22, IL-34, IL-35, CXCL-2, CXCL-10, and CXCL-13, and multivariate analysis confirmed a strong association (r2: 0.47) with both CXCL-2 (β: -0.965, p = 0.0052) and CXCL-13 (β: 0.241, p = 0.018). This latter cytokine increased in RRMS with high HRF count compared with NIND and RRMS with low HRF count. Finally, the CXCL-13/CXCL-2 ratio strongly associated with HRF count (r: 0.8, p < 0.005) and cortical lesion volume (r: 0.5, p < 0.05). Conclusions The association of HRF with intrathecally produced monocyte/microglia-derived cytokines confirms their microglial origin and indicates they are worth further evaluating as markers of activated microglia.